The Women’s Art Society of Montreal and Its Place in History, 1894-2019 - Keays, Cathy (Autoédition, 2019)
The Women's Art Society of Montreal (WASM) was founded in 1894 by two Montrealers, Mrs. James H. Peck (nee Mary Alice Skelton) and Mary Martha (May) Phillips, with the goal of integrating women into the art world. This organization was the Montreal branch of the Toronto-based Women’s Art Association until 1907, when it broke away from the mother organization to form its own independent Women’s Art Society of Montreal. In 1938, the Society’s efforts shifted towards entertainment and other branches of the arts, such as theatre, music and studio art. In 1981, the Society officially adopted a French name: l’Association culturelle des femmes de Montréal, but the organization remained essentially an English support group. In 1998 it began to accept men as members. The author traces the local, national and international events that coincided with each year of the WASM's existence.
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; discipline; groupes de femmes; histoire; histoire des femmes*; montréal; périodes historiques; régions géographiques; sciences humaines; thématiques; travail